Back Cover: Benzylphenylpyrrolizinones with Anti‐amyloid and Radical Scavenging Effects, Potentially Useful in Alzheimer's Disease Treatment (ChemMedChem 12/2017). (21st June 2017) - Jourdan, Jean‐Pierre; Since, Marc; El Kihel, Laïla; Lecoutey, Cédric; Corvaisier, Sophie; Legay, Rémi; Sopková‐de Oliveira Santos, Jana; Cresteil, Thierry; Malzert‐Fréon, Aurélie; Rochais, Christophe; Dallemagne, Patrick
Abstract : The back cover picture shows a novel benzylphenylpyrrolizinone agent designed to target both the amyloid aggregation and the oxidative stress implied in the pathogenesis of Alzheimer's Disease. Associated to radical scavenging effects and relevant druggability parameters, these properties could contribute to slow down neurodegeneration and to stem brain damages induced by the disease. Further in vivo experiments will be carried out in this respect to confirm the potential therapeutic interest of this novel series of derivatives. More information can be found in the Communication by Jean‐Pierre Jourdan, Christophe Rochais, Patrick Dallemagne et al. onpage 913 in Issue 12, 2017 (DOI:10.1002/cmdc.201700102 ).